The macroanatomy of vertebral column and thorax skeleton in chinchillas - Vural ÖZDEMİR; Aysun ÇEVİK DEMİRKAN; İsmail TÜRKMENOĞLU (Eurasian Journal of Veterinary Sciences)
ln this study, it was exceminated bones which consisted of the vertebral column and thorax in chinchilla. It was determined that chinchilla had C7,T14,L6,S2,C22 vertebras. Atlas has foramen vertebrale laterale, foramen alare and foramen transversarium. Proccessus transversus of axis is well expanded. It was observed that anticlinal vertebra was 11. vertebra and Processus accessroius was present only in L1-L4 vertebra. Proccessus transversus and corpus of sacral vertebra only were joined one another.lt was found out that ossa arcus hemalis were present ventral aspect of joints which were consisted of vertebra between S2 and S10. The body of the sternum was consisted of 5 sternebras.